GPS and PSI integration for monitoring urban land motion - Leighton, Jonathan M (2010)
Urban ground motion due to natural or man-made geological processes is an issue of major importance for local authorities, property developers, planners and buyers. Increased knowledge of this phenomena would benefit all involved but the measurement techniques in common use have either spatial or temporal inadequacies. A technique known as Persistent Scatterer Interferometry (PSI) has been developed which can map ground motion to high precision over large areas with a temporal scale measured in years. PSI takes advantage of the high number of Synthetic Aperture Radar (SAR) images available to mitigate the atmospheric effects that inhibit standard Interferometric SAR (InSAR) techniques. This however involves assumptions about the nature of atmospheric variability, such as its randomness over time, or its spatial extent. In addition, little is known about the Persistent Scatterers (PS) themselves and PSI is only able to provide results relative to a reference PS. The reference PS point is often arbitrarily chosen and may itself be in an area undergoing ground motion, thus adding a degree of ambiguity to any relatively derived motion. The purpose of this work is to investigate possible solutions to these shortfalls and quantify any improvements made.